Magnetized MXene / metal nanowire composite electromagnetic shielding film material and preparation method thereof
By wrapping the magnetic metal shell layer on the surface of MXene and overlapping metal nanowires to form a multi-interface structure, the problems of high density and low absorption efficiency of traditional metal electromagnetic shielding materials are solved, and the electromagnetic shielding performance is improved and electromagnetic pollution is reduced.
Patent Information
- Application Number
- CN202411371343.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
AI Technical Summary
Traditional metal electromagnetic shielding materials have high density and low absorption efficiency, which leads to electromagnetic wave reflection, affecting electromagnetic shielding performance, and highly conductive materials are prone to electromagnetic pollution.
Magnetic MXene/metal nanowire composite electromagnetic shielding film material is used to encapsulate the magnetic metal shell layer on the surface of the MXene and overlap the metal nanowires to form a multi-interface structure to enhance electromagnetic wave absorption and conductivity.
The electromagnetic shielding performance is improved, electromagnetic wave reflection is reduced, the stability of the material is enhanced, and the electromagnetic wave absorption capacity is improved through multiple reflection and magnetic loss mechanisms, reducing environmental pollution.
Smart Images

Figure HDA0005067662410000011 
Figure HDA0005067662410000012 
Figure HDA0005067662410000013
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electromagnetic interference shielding materials, and in particular to a magnetic MXene / metal nanowire composite electromagnetic shielding film material and a preparation method thereof. Background Art
[0002] With the widespread use of electronic devices such as smartphones, tablets, computers and other communication devices, it has brought great convenience to people while also bringing serious electromagnetic pollution problems. Many electronic devices are extremely sensitive to the electromagnetic environment, and their normal operation requires a highly stable and interference-free electromagnetic environment. Electromagnetic shielding can prevent external electromagnetic interference from entering the device, ensuring the accuracy and stability of the device's measurement. In the field of communications, high-frequency circuits in equipment such as mobile phone base stations and satellite communication ground stations are easily interfered by external electromagnetic signals, thereby affecting the signal transmission quality and communication stability. Electromagnetic shielding can effectively reduce this interference and ensure smooth communication. For this reason, electromagnetic shielding materials have become a current research hotspot.
[0003] Most of the research on electromagnetic shielding materials focuses on traditional metal materials, which have very good electromagnetic shielding performance due to their good electrical conductivity. However, traditional metal materials also have many problems, such as too high density to meet the lightweight requirements, low absorption efficiency of metal materials, and electromagnetic shielding efficiency mainly based on reflection, which limits the application of metal-based electromagnetic shielding materials. MXene is a type of material with a two-dimensional layered structure. Due to its excellent electrical conductivity and unique spatial structure, it has shown great application potential in electromagnetic shielding, energy storage, adsorption and sensors. Magnetic metals (Fe, Co, Ni) have strong magnetic properties and can have a strong magnetic loss effect on electromagnetic waves. The construction of core-shell structure is also conducive to the formation of interface polarization at the heterogeneous interface of the two materials to enhance the absorption of electromagnetic waves. Copper nanowires have good electromagnetic shielding performance due to their excellent electrical conductivity. However, the high electrical conductivity of copper nanowires, MXene materials and magnetic metals often leads to higher reflection shielding, resulting in a large amount of electromagnetic pollution. Therefore, it is necessary to reduce the reflection of electromagnetic waves and improve the electromagnetic wave absorption capacity of materials through structural design. Summary of the invention
[0004] The main purpose of the present invention is to provide a magnetic MXene / metal nanowire composite electromagnetic shielding film material, wherein the magnetic MXene is a multi-interface shell structure with MXene as the core and a magnetic material shell wrapped on the MXene surface to form a multi-interface complex electromagnetic reflection and absorption heterostructure of MXene-magnetic metal-air gap, while the metal nanowires overlap the magnetic MXene to form a conductive network with good conductivity.
[0005] Furthermore, the metal nanowires include one or more of copper, silver, gold, aluminum, nickel, zinc, platinum, titanium, and vanadium.
[0006] Furthermore, the magnetic material includes one or more of iron, cobalt and nickel.
[0007] Another object of the present invention is to provide a method for preparing a magnetic MXene / metal nanowire composite electromagnetic shielding film material, comprising the following steps:
[0008] 1) Dispersing MXene in oleylamine, adding metal nanowire precursors, and growing metal nanowires between MXene;
[0009] 2) Adding magnetic metal precursors to the reaction system to react and coat the surface of MXene with a magnetic material shell;
[0010] 3) transferring the reaction product to a filter membrane by vacuum filtration;
[0011] 4) Perform vacuum annealing to obtain a magnetic MXene / metal nanowire composite electromagnetic shielding film material.
[0012] Optionally, step 1) includes: mixing MXene powder, oleylamine, cupric chloride powder and first nickel acetylacetonate powder, heating to 75-85° C. for 5-15 min, then raising the temperature to 180-190° C. for 3-5 h, and growing copper nanowires between the MXenes.
[0013] Optionally, the ratio is MXene powder: cupric chloride powder: first nickel acetylacetonate powder: oleylamine = (0.1-0.3) g: (0.7-0.9) mmol: (0.3-0.5) mmol: 10 ml.
[0014] Optionally, step 1) is performed in an inert gas atmosphere.
[0015] Optionally, in step 2), a second nickel acetylacetonate powder is added to the reaction system, and the temperature is maintained at 180-190° C. for 45-65 min to coat the Ni shell layer on the surface of the MXene.
[0016] Optionally, the ratio is MXene powder: second acetylacetonate nickel powder = (0.1-0.3) g: (0.7-0.9) mmol.
[0017] Optionally, the annealing temperature of the vacuum annealing is 180° C. to 220° C., and the annealing time is 20 to 40 minutes.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] The magnetized MXene / metal nanowire composite electromagnetic shielding film material of the present invention first grows copper nanowires between MXenes using a one-pot method, and then wraps a layer of magnetic metal (Fe, Co, Ni) shell from the surface of MXene. The conductive network formed by the overlap of copper nanowires and core-shell structure MXene has good conductivity and can reflect a large amount of electromagnetic waves. At the same time, the core-shell structure MXene realizes a composite structure of magnetic metal-MXene-magnetic metal. Electromagnetic waves will be reflected multiple times in this complex structure and then dissipated. The heterogeneous interface between magnetic metal and MXene will also cause enhanced electromagnetic wave absorption. The magnetic loss mechanism brought by the magnetic metal can also enhance electromagnetic wave absorption. The wrapping of magnetic metal also improves the stability of MXene materials to a certain extent.
[0020] The multi-interface structure of the novel nano-network of the present invention utilizes the composition of interfaces of different materials to play the role of ohmic loss, multiple reflection, interface polarization, magnetic loss, etc. on electromagnetic waves, and can be used to make high-performance electromagnetic shielding films, and then realize the application in electronic equipment. The film has excellent electromagnetic shielding performance and brings unprecedented new applications to the field of electronic equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0022] Figure 1 This is a process flow chart for preparing the magnetic MXene / metal nanowire composite electromagnetic shielding film material of the embodiment;
[0023] Figure 2 A schematic diagram of the structure of a magnetic MXene / metal nanowire composite electromagnetic shielding film material according to an embodiment;
[0024] Figure 3 This is a SEM image of the magnetic MXene / metal nanowire composite electromagnetic shielding film material of Example 1;
[0025] Figure 4 This is the XPS spectrum of the magnetic MXene / metal nanowire composite electromagnetic shielding film material of Example 1;
[0026] Figure 5 This is the XRD spectrum of the magnetic MXene / metal nanowire composite electromagnetic shielding film material of Example 1;
[0027] Figure 6 It is a schematic diagram for comparing the electromagnetic wave absorption performance tests of the magnetic MXene / metal nanowire composite electromagnetic shielding film material of Example 1, the pure copper nanowire material of Comparative Example 1, and the copper nanowire / MXene of Comparative Example 2;
[0028] Figure 7It is a schematic diagram for comparing the electromagnetic shielding performance tests of the magnetic MXene / metal nanowire composite electromagnetic shielding film material of Example 1, the pure copper nanowire material of Comparative Example 1, and the copper nanowire / MXene of Comparative Example 2;
[0029] Figure 8 Schematic diagram showing the comparison of the conductivity tests of the magnetized MXene / metal nanowire composite electromagnetic shielding film material of Example 1, the pure copper nanowire material of Comparative Example 1, and the copper nanowire / MXene of Comparative Example 2. DETAILED DESCRIPTION
[0030] The preparation method of the magnetic MXene / metal nanowire composite electromagnetic shielding film material comprises the following steps:
[0031] (1) Synthesizing metal nanowires between MXene materials;
[0032] (2) Using the corresponding metal precursors to coat the magnetic metal shell on the MXene surface;
[0033] (3) The material grown in step (2) is washed with an organic solvent and transferred to filter paper by vacuum filtration to form an electromagnetic shielding film.
[0034] (4) Annealing under vacuum to remove residual organic matter on the surface of the electromagnetic shielding film.
[0035] Example 1
[0036] refer to Figure 1 The specific steps of the preparation method of the magnetic MXene / metal nanowire composite electromagnetic shielding film material of Example 1 are as follows:
[0037] 1. First, copper nanowires are grown between MXene using a hydrothermal method.
[0038] Specifically:
[0039] 0.2g of MXene powder, 0.8mmol of copper chloride powder, 0.4mmol of nickel acetylacetonate powder and 10ml of oleylamine were measured by analytical balance, placed in a three-necked flask and mixed, and then the entire three-necked flask reaction device was placed on a constant temperature heating magnetic stirrer. First, the entire reaction device was heated to 85℃ and maintained for 15min. At this time, part of the nickel ions were first reduced to nickel atoms by oleylamine. Then the reaction temperature was raised to 185℃ and maintained for 4h. At this time, nickel ions and copper ions were simultaneously reduced to nickel atoms and copper atoms. At the same time, the remaining copper ions were reduced by nickel atoms, and nickel atoms were oxidized to nickel ions. Due to the passivation effect of oleylamine on the (111) crystal plane of copper grains, copper will grow along the (100) crystal plane to form copper nanowires. In the reaction system, oleylamine serves as a structure directing agent, a reducing agent, and a dispersant, and nickel acetylacetonate serves as a catalyst.
[0040] During the reaction, 50 sccm of high-purity nitrogen was continuously passed through the entire reaction device to prevent the introduction of oxygen during the reaction process and oxidation of the growing copper nanowires.
[0041] 2. Use the corresponding metal precursor to wrap the magnetic metal shell on the MXene surface
[0042] The system maintained a reaction temperature of 185°C, and 0.8 mmol of nickel acetylacetonate powder was measured using an analytical balance and added to a three-necked flask for reaction for 1 hour. The added nickel acetylacetonate would decompose in oleylamine and be reduced to nickel atoms. Under the guidance of oleylamine, nickel atoms would deposit on the surface of MXene to form a metal shell.
[0043] 3. Use organic solvent to clean the material and transfer it to filter paper by vacuum filtration to make electromagnetic shielding film.
[0044] After the mixture with completed core-shell structure MXene growth is cooled to room temperature, it is subjected to ultrasonic and centrifugal purification in sequence, and the precipitate is taken. The magnetized MXene / metal nanowires are transferred to filter paper using vacuum filtration equipment. Under the action of vacuum filtration, the copper nanowires and the magnetized MXene are overlapped to form a conductive channel.
[0045] 4. Use vacuum annealing to remove residual organic matter on the surface of the electromagnetic shielding film.
[0046] The filter paper with the transferred magnetic MXene / metal nanowire material was placed in a CVD, evacuated and heated to 200°C, reacted for 30 minutes and then taken out to obtain a magnetic MXene / metal nanowire composite electromagnetic shielding film material, represented by Cu NWs / MXene@Ni.
[0047] The prepared magnetic MXene / metal nanowire composite electromagnetic shielding film material, such as Figure 2 As shown, the magnetized MXene is a multi-interface shell structure, with MXene 2 as the core and a magnetic material shell 3 wrapped on the surface of MXene 2, forming a multi-interface complex electromagnetic reflection absorption heterostructure of MXene-magnetic metal-air gap. At the same time, the metal nanowire 1 overlaps the magnetized MXene to form a conductive network with good conductivity.
[0048] refer to Figure 3 SEM image of magnetic MXene / metal nanowire composite electromagnetic shielding film material. Figure 3 It can be seen that after being wrapped with metallic nickel, the surface of MXene changes from its original smoothness to roughness.
[0049] Figure 4The XPS spectrum shows the presence of Cu, Ti, C, and Ni elements on the surface of the sample, which proves the successful synthesis of copper nanowires and the successful wrapping of metallic nickel on the surface of MXene.
[0050] Figure 5 The XRD spectrum shows the presence of Cu and Ni elements in the sample, which proves the successful synthesis of copper nanowires and the successful wrapping of metallic nickel on the surface of MXene.
[0051] Comparative Example 1
[0052] 1. First, grow copper nanowires using a hydrothermal method.
[0053] 0.8mmol of copper chloride powder, 0.4mmol of nickel acetylacetonate powder and 10ml of oleylamine were measured by analytical balance, placed in a three-necked flask and mixed, and then the entire three-necked flask reaction device was placed on a constant temperature heating magnetic stirrer. First, the entire reaction device was heated to 85℃ and maintained for 15min. At this time, part of the nickel ions were first reduced to nickel atoms by oleylamine. Then the reaction temperature was raised to 185℃ and maintained for 4h. At this time, the nickel ions and copper ions were simultaneously reduced to nickel atoms and copper atoms. At the same time, the remaining copper ions were reduced by nickel atoms, and the nickel atoms were oxidized to nickel ions. Due to the passivation effect of oleylamine on the (111) crystal plane of copper grains, copper will grow along the (100) crystal plane to form copper nanowires. In the reaction system, oleylamine serves as a structure directing agent, a reducing agent, and a dispersant, and nickel acetylacetonate serves as a catalyst.
[0054] During the reaction, 50 sccm of high-purity nitrogen was continuously passed through the entire reaction device to prevent the introduction of oxygen during the reaction process and oxidation of the growing copper nanowires.
[0055] 2. Use organic solvent to clean the material and transfer it to filter paper by vacuum filtration to make electromagnetic shielding film.
[0056] After the mixture on which the copper nanowires have grown is cooled to room temperature, it is subjected to ultrasonic and centrifugal purification in sequence, and the precipitate is taken. The copper nanowires are transferred to filter paper using a vacuum filtration device, and under the action of vacuum filtration, the copper nanowires overlap each other to form a conductive channel.
[0057] 3. Use vacuum annealing to remove residual organic matter on the surface of the electromagnetic shielding film.
[0058] The filter paper with the copper nanowire material transferred was placed in a CVD and evacuated and heated to 200°C. After reacting for 30 minutes, the filter paper was taken out to obtain a copper nanowire composite electromagnetic shielding film material, represented by Cu NWs.
[0059] Comparative Example 2
[0060] 1. First, grow copper nanowires using a hydrothermal method.
[0061] 0.2g of MXene powder, 0.8mmol of copper chloride powder, 0.4mmol of nickel acetylacetonate powder and 10ml of oleylamine were measured by analytical balance, placed in a three-necked flask and mixed, and then the entire three-necked flask reaction device was placed on a constant temperature heating magnetic stirrer. First, the entire reaction device was heated to 85℃ and maintained for 15min. At this time, part of the nickel ions were first reduced to nickel atoms by oleylamine. Then the reaction temperature was raised to 185℃ and maintained for 4h. At this time, nickel ions and copper ions were simultaneously reduced to nickel atoms and copper atoms. At the same time, the remaining copper ions were reduced by nickel atoms, and nickel atoms were oxidized to nickel ions. Due to the passivation effect of oleylamine on the (111) crystal plane of copper grains, copper will grow along the (100) crystal plane to form copper nanowires. In the reaction system, oleylamine serves as a structure directing agent, a reducing agent, and a dispersant, and nickel acetylacetonate serves as a catalyst.
[0062] During the reaction, 50 sccm of high-purity nitrogen was continuously passed through the entire reaction device to prevent the introduction of oxygen during the reaction process and oxidation of the growing copper nanowires.
[0063] 2. Use organic solvent to clean the material and transfer it to filter paper by vacuum filtration to make electromagnetic shielding film.
[0064] After the grown copper nanowire / MXene mixture is cooled to room temperature, it is subjected to ultrasonic and centrifugal purification in sequence, and the precipitate is taken. The copper nanowire / MXene is transferred to filter paper using a vacuum filtration device. Under the action of vacuum filtration, the copper nanowire and MXene overlap each other to form a conductive channel.
[0065] 3. Use vacuum annealing to remove residual organic matter on the surface of the electromagnetic shielding film.
[0066] The filter paper with the copper nanowire / MXene material transferred was placed in a CVD and evacuated and heated to 200°C. After reacting for 30 minutes, the filter paper was taken out to obtain a copper nanowire / MXene composite electromagnetic shielding film material, represented by Cu NWs / MXene.
[0067] Figure 6 The thin films of Example 1, Comparative Example 1 and Comparative Example 2 were tested by a vector network analyzer, and the absorption loss SEA was calculated using the waveguide method using the data of S11 and S21. It can be seen from the figure that the absorption loss of the magnetic MXene / metal nanowires wrapped with a nickel shell in Example 1 is higher.
[0068] Figure 7The films of Example 1, Comparative Example 1 and Comparative Example 2 were tested by a vector network analyzer, and the total shielding effectiveness SE was calculated using the waveguide method using the data of S11 and S21. It can be seen from the figure that the magnetic MXene / metal nanowires wrapped with a nickel shell in Example 1 have higher electromagnetic shielding effectiveness.
[0069] Figure 8 The surface square resistance of the thin films of Example 1, Comparative Example 1 and Comparative Example 2 was tested by a four-probe station. The magnetic MXene / metal nanowires wrapped with a nickel shell layer in Example 1 had the smallest resistance and the best conductivity.
[0070] The simple preparation method of the magnetized MXene / metal nanowires in the present invention is used to wrap MXene and magnetic metal together, introducing magnetic loss mechanism and polarization loss mechanism, which improves the overall electromagnetic shielding performance while reducing the proportion of reflected electromagnetic waves and reducing secondary pollution to the environment.
[0071] The above embodiments are only used to further illustrate a magnetic MXene / metal nanowire composite electromagnetic shielding film material and a preparation method thereof of the present invention, but the present invention is not limited to the embodiments. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention shall fall within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a magnetic MXene / metal nanowire composite electromagnetic shielding film material, characterized in that: The following steps are involved: 1) Dispersing MXene in oleylamine, adding metal nanowire precursors, and growing metal nanowires between MXene; 2) Adding magnetic metal precursors to the reaction system to react and coat the surface of MXene with a magnetic material shell; 3) transferring the reaction product to a filter membrane by vacuum filtration; 4) Perform vacuum annealing to obtain a magnetic MXene / metal nanowire composite electromagnetic shielding film material.
2. The method for preparing the magnetic MXene / metal nanowire composite electromagnetic shielding film material according to claim 1, characterized in that: The metal nanowires include one or more of copper, silver, gold, aluminum, nickel, zinc, platinum, titanium, and vanadium.
3. The method for preparing the magnetic MXene / metal nanowire composite electromagnetic shielding film material according to claim 1, characterized in that: The magnetic material includes one or more of iron, cobalt and nickel.
4. The method for preparing the magnetic MXene / metal nanowire composite electromagnetic shielding film material according to claim 1, characterized in that: Step 1) comprises: mixing MXene powder, oleylamine, cupric chloride powder and first nickel acetylacetonate powder, heating to 75-85° C. for 5-15 min, then raising the temperature to 180-190° C. for 3-5 h, and growing copper nanowires between the MXenes.
5. The method for preparing the magnetic MXene / metal nanowire composite electromagnetic shielding film material according to claim 4, characterized in that: The ratio is MXene powder: cupric chloride powder: first acetylacetonate nickel powder: oleylamine = (0.1-0.3) g: (0.7-0.9) mmol: (0.3-0.5) mmol: 10 ml.
6. The method for preparing the magnetic MXene / metal nanowire composite electromagnetic shielding film material according to claim 4, characterized in that: Step 1) is performed in an inert gas atmosphere.
7. The method for preparing the magnetic MXene / metal nanowire composite electromagnetic shielding film material according to claim 4, characterized in that: In step 2), a second nickel acetylacetonate powder is added to the reaction system, and the temperature is maintained at 180-190° C. for 45-65 min to coat the Ni shell layer on the surface of the MXene.
8. The method for preparing the magnetic MXene / metal nanowire composite electromagnetic shielding film material according to claim 7, characterized in that: The ratio is MXene powder: second acetylacetonate nickel powder = (0.1-0.3) g: (0.7-0.9) mmol.
9. The method for preparing the magnetic MXene / metal nanowire composite electromagnetic shielding film material according to claim 1, characterized in that: The vacuum annealing has an annealing temperature of 180° C. to 220° C. and an annealing time of 20 to 40 minutes.
10. The magnetic MXene / metal nanowire composite electromagnetic shielding film material prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The magnetized MXene is a multi-interface shell structure, with MXene as the core and a magnetic material shell wrapped on the MXene surface to form a multi-interface complex electromagnetic reflection and absorption heterostructure of MXene-magnetic metal-air gap. At the same time, metal nanowires overlap the magnetized MXene to form a conductive network.
